Herpes simplex virus type 2 inhibits TNF-α-induced NF-κB activation through viral protein ICP22-mediated interaction with p65 - Hu, Huimin; Fu, Ming; Li, Chuntian; Zhang, Binman; Li, Yuncheng; Hu, Qinxue; Zhang, Mudan (Frontiers in Immunology, 2022)
Herpes simplex virus type 2 (HSV-2) is a prevalent human pathogen and the main cause of genital herpes. After initial infection, HSV-2 can establish lifelong latency within dorsal root ganglia by evading the innate immunity of the host. NF-κB has a crucial role in regulating cell proliferation, inflammation, apoptosis, and immune responses. It is known that inhibition of NF-κB activation by a virus could facilitate it to establish infection in the host. In the current study, we found that HSV-2 inhibited TNF-α-induced activation of NF-κB-responsive promoter in a dose-dependent manner, while UV-inactivated HSV-2 did not have such capability. We further identified the immediate early protein ICP22 of HSV-2 as a vital viral element in inhibiting the activation of NF-κB-responsive promoter. The role of ICP22 was confirmed in human cervical cell line HeLa and primary cervical fibroblasts in the context of HSV-2 infection, showing that ICP22 deficient HSV-2 largely lost the capability in suppressing NF-κB activation. HSV-2 ICP22 was further shown to suppress the activity of TNF receptor-associated factor 2 (TRAF2)-, IκB kinase α (IKK α)-, IKK β-, IKK γ-, or p65-induced activation of NF-κB-responsive promoter. Mechanistically, HSV-2 ICP22 inhibited the phosphorylation and nuclear translocation of p65 by directly interacting with p65, resulting in the blockade of NF-κB activation. Furthermore, ICP22 from several alpha-herpesviruses could also inhibit NF-κB activation, suggesting the significance of ICP22 in herpesvirus immune evasion. Findings in this study highlight the importance of ICP22 in inhibiting NF-κB activation, revealing a novel mechanism by which HSV-2 evades the host antiviral responses.